PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI DALAM MENINGKATKAN KINERJA KARYAWAN PT BANK RAKYAT INDONESIA (PERSERO) TBK. KC TAKALAR UNIT PATTALLASSANG - Muliadi, Siti Nur Aisyah (Universitas Teuku Umar, 2024)
This study analyzes the influence of leadership style and motivation on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk., Takalar Branch Office, Pattallassang Unit. Employee performance is crucial in achieving the banking company's goals. The quantitative research method used was multiple linear regression. Data were obtained from employee questionnaires and tested for validity, reliability, classical assumptions, t-tests, and F-tests. The results showed that leadership style and motivation have a significant, partial positive effect on employee performance. Leadership style has a calculated t-value of 2.219 (> t-table 2.040) with a significance level of 0.034 (<0.05). Motivation is also significant with a calculated t-value of 2.169 (> t-table 2.040) and a significance level of 0.038 (<0.05). Overall, the R-square of 0.397 indicates that 39.7% of the variation in employee performance is explained by these two variables.Keywords : Leadership Style, Motivation, Employee Performance.